Aussiedler Mortality (AMOR): cohort studies on ethnic German migrants from the former Soviet Union - Winkler, Volker; Kaucher, Simone; Deckert, Andreas; Becher, Heiko (BMJ open, 2019)
Purpose: The Aussiedler Mortality cohorts represent the unique migrant group of ethnic Germans (resettlers) from the former Soviet Union who migrated to Germany mainly after the fall of the iron curtain in 1989. Resettlers are the second largest migrant group in Germany and their health status was largely unknown before the cohorts were set up. - Participants: Four retrospective register-based cohorts were set up in different federal states of Germany, each focussing on different health aspects. In total, the cohorts include 92 362 resettlers (men: 51.5%, women: 48.5%) who immigrated between 1990 and 2005 with a mean age at immigration of 36.6 years (range 0-105 years). Resettlers are of German ancestry and they are immediately granted the German citizenship with all rights and duties. - Findings to date: Vital status and causes of death (International Classification of Diseases codes based on death certificates or record linkage) were collected for three cohorts as well as cancer incidence and incidence of acute myocardial infarction in three of the cohorts. Currently, an observation period of 20 years (1990-2009) is covered. Overall mortality among resettlers was surprisingly lower in comparison to the German population with standardised mortality ratios of 0.87 (95% confidence limits 0.84-0.91) for women and 0.96 (0.92-0.99) for men, and even stronger for cardiovascular diseases (women: 0.84 (0.79-0.89); men: 0.80 (0.75-0.86). However, observed differences can neither be explained by the ‘healthy migrant effect’ nor by common behavioural risk factors and may be related to factors which have not yet been studied. - Future plans: The existing cohorts will be continued and prospective studies on resettlers are underway: one cohort will be followed-up prospectively and two other large prospective cohort studies in Germany will be used for a detailed assessment of lifestyle, environmental and genetic/epigenetic factors on the mortality and morbidity pattern of resettlers.
Gesehen am 04.04.2019